Importance of foot and mouth disease vaccine purity in interpreting serological surveys - Smitsaart, E. (2015)
The aim of this study was to determine whether the degree of purity achieved in conventional vaccines against the foot and mouth disease virus in Argentina interferes with the interpretation of seroepidemiological surveys for confirming the absence of viral activity, which are performed to support the recognition of free zones practising vaccination. The evaluation of 168 vaccine series due to be marketed in Argentina (2006–2012) and subjected to official control testing in cattle, as well as repeated vaccination of cattle and other species using vaccines with high antigen concentrations, demonstrated that they did not induce antibodies to non-structural proteins (NSPs). The results show clearly that vaccines with satisfactory potency do not induce a response to NSPs, even by forcing the immune response through more concentrated doses with multiple valences and revaccination protocols at shorter intervals than in vaccination campaigns. These results confirm that the vaccines used in routine vaccination programmes have a degree of antigen purification consistent with the needs observed on the basis of sampling for serological surveillance. Moreover, serological surveys conducted in 2006–2011 by Argentina’s official Veterinary Services – the National Health and Agrifood Quality Service (SENASA) – on more than 23,000 sera per year from cattle included in the vaccination programme, in order to confirm the absence of virus circulation, revealed an average 0.05% of reactive results, consistent with the specificity of the tests. In conclusion, the vaccines produced by conventional methods and with proven potency that are available in Argentina are sufficiently purified to ensure that they do not interfere with the interpretation of sampling for serological surveillance performed to support the recognition of FMD-free zones practising vaccination.